Babantu ababomvu entliziyweni(People who are 'Red' in their hearts) and the myth of 'modernity' - Haynes, Duncan Robert (Rhodes University, Faculty of Humanities, Department of Anthropology)
This study examines a history of urban research on ancestral belief of amaXhosa within the Greater East London region, Eastern Cape, South Africa which spanned much of the 20th century (1934"“2002). Through extensive textual and literary investigation, this thesis offers new perspectives on this topic. Current theoretical explorations offer the tools to reassess the positionality of the researchers and in light of findings of these previous studies, highlighting above all, the presence of certain academic 'blind-spots'. These 'blind-spots' are argued to have been caused by theoretical and methodological constraints, particularly around Western-centric definitions of the nature of 'modernity' that rely on the positivist notion of a singular unilinear path of time as a universal standard (and which thus defines 'progressiveness' and 'backwardness'). (These 'blind spots' were notably further strengthened by a Eurocentric interpretation of identity and a trend of Neo-Marxist scholarship between the 1970s and the 2010s1 which created a 'taboo' on addressing issues of culture, and especially of ancestral spirituality, as this was taken to be portraying Africans as culturally 'static' and backward and therefore supporting Apartheid ideologies of 'separate development'). Through these textual investigations this thesis brings to light the, largely unrecognised, core of the issue or driving factor behind the difficulties in all of these previous studies. This is posited as the existence of a prevailing culture of 'silence' in Xhosa spaces (stretching from 1840"“2000) regarding the sustained importance of 'Redness' (ancestral spirituality and traditional dimensions of identity due to the notion that it was 'backward'). This self-censoring is unpacked as having been an expedient response by many to the requirements for Xhosa pagans to wash off the symbolic red cosmetic clay at baptism, put on 'decent' Western clothing and shoes and take on Christian first names ('shedding' their previous names and identities) as processes deemed necessary to properly convert to Christianity (Frescura, 2015). More significantly however, it has been argued by scholars that adopting Christianity was the only way to be able to harness the power of education at a time of starvation related to the famine of the millennial Cattle Killing movement (1856"“7) and the Xhosa military defeat at the end of the 100-year period of the British Xhosa Frontier Wars (1779"“1879). This thesis uses perspectives offered by Queer theory to unpack the pain of this 'veiling' of aspects of identity as a necessary strategy for achieving economic 'success' amid the structural and epistemological violence of colonialism and apartheid. It is suggested that a combination of the 'silence' and 'taboo' area of the 'blind-spot' could completely 'veil' these epistemological realities from the view of many earlier researchers of urban Xhosa identity (whose cultural and linguistic backgrounds as well as etic positioning caused them to be unable to 'knock' to gain access into this normally 'veiled' world). This thesis combines these historical perspectives with contemporary scholarship and literary works to propose that these 'Red' aspects of identity and spirituality have always and still 'continue' to form a core, or crux, of Xhosa identity for a previously widely unrecognised and overwhelming majority of urban amaXhosa. This thesis uses the perspective offered by a Xhosa translation of the title of Mda's English language novel, 'A Heart of Redness' (2000), to explore the importance of ancestral spirituality and clan identities to amaXhosa as a [previously invisible/veiled] 'Redness of one's Heart' for a high proportion of contemporary amaXhosa. In this way, this thesis agrees with scholars such as Latour (1993) and Mignolo (2007) in their 'jarring' expose regarding the epistemic violence of euro-normative notions of 'modernity'. Here they call for a disruption of the pervasive idea of the West as being at the 'forefront' of human experience and even a challenge to the western reading of time. Finally, through exploring critique of the 'Secularisation Thesis' of the Western world, this thesis poses the implicit question contained in its title: 'Is the western world now perhaps able to embrace a 'modernity' and integrative-cosmology that has been safe-guarded by Xhosa pagans since the 1840s?' This study documented numerical indicators on the presence of ancestral belief and traditional dimensions of Xhosa identity from fieldwork conducted in an urban locality King William's Town (Qonce) within the Buffalo City Municipality, Eastern Cape of South Africa from September 2018 to December 2019. In-depth quantitative and qualitative data were collected from lengthy interactions with 305 consenting Xhosa participants. These interactions comprised 129 semi-structured and 176 structured interviews, 61 of the latter formed the sample for numerical data analysis with which to give clarity on the abiding importance of ancestral spirituality for a vast majority of urban amaXhosa.
Keywords: Xhosa (African people) Religious life; Ancestor worship; Epistemic violence; Christianity and Paganism; Decoloniality